Pengaruh Hydrocooling dan Jenis Plastik Terhadap Mutu Jagung Manis (Zea mays L. Saccharata) Selama Penyimpanan Dingin - Sarasulistian, Ni Luh Putu; Pratiwi Pudja, Ida Ayu Rina; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 10 No 1 (2022): April, 2021)
ABSTRAK Hydrocooling  merupakan cara sederhana untuk menurunkan suhu bahan pangan secara cepat sampai suhu bahan mendekati suhu penyimpanan yang akan dilakukan. Selain itu, perlakuan pengemasan bahan pangan mampu menghambat laju susut bobot dan kualitas produk. Rancangan Acak Lengkap (RAL) yang terdiri dari dua faktor. Faktor pertama adalah lama perendaman pada proses hydrocooling (tanpa perendaman, perendaman selama 60 detik, dan perendaman 120 detik (suhu air perendaman 5 o C )) dan faktor kedua adalah jenis plastik (jenis plastik Polypropylene (PP)  dan plastik High Density Polyethylene (HDPE)). Setiap unit percobaan dilakukan pengulangan sebanyak 3 kali dan semua unit percobaan disimpan pada lemari pendingin dengan suhu 10 o C .  Parameter diamati adalah a) susut bobot b) kekerasan bahan, c) warna, d) kadar air, e) laju pendinginan. Pengamatan dilakukan selama 8 hari dengan interval pengambilan data selama 2 hari sekali. Hasil pengamatan selama 8 hari menunjukan kombinasi perlakuan terbaik diperoleh pada perlakuan  hydrocooling selama 2 menit dengan kemasan Polypropylene (H2P1) sebagai dengan jagung manis yang disimpan mengalami susut bobot 0,33%, kekerasan 34,20 N, warna L 50.00, a 16.69, b 51.81, kadar air 74,167%, dan laju pendinginan 2.3982 o C/30 menit. ABSTRACT  Hydro cooling is a simple way to quickly lower the temperature of the food until the material temperature near the storage temperature. In addition, food packaging treatment can inhibit the rate of weight loss and product quality. This study used a completely randomized design (CRD) which consisted of two factors. The first factor was the immersion time in the hydrocooling process (without soaking, 1 minute immersion, and 2 minutes of immersion (immersion water temperature 5 o C ± 1)) and the second factor was the type of plastic (Polypropylene (PP) plastic-type and High-Density Polyethylene (HDPE) plastic). Each experimental unit was repeated 3 times and all experimental units were stored in a refrigerator with a temperature of 10 o C ± 1. The parameters observed were a) moisture content, b) weight loss, c) material hardness, d) color, and e) cooling rate. Observations were made for 8 days with data retrieval intervals for 2 days. During cold storage sweet corn undergoes many physical changes. These changes began to appear on the 6th day. On the 6th day, sweet corn stored in cold storage experienced physical changes, namely wilting, wrinkling, starting to pale, and brownish color appeared at the tip to the base of the surface of the sweet corn. On the 8th day sweet corn experienced a decrease in weight loss and moisture content in the treatment without hydro cooling and without packaging, while the hydro cooling treatment (1 minute and 2 minutes) and packed (with Polypropylene (PP) plastic and High-Density Polyethylene plastic (HDPE) also experienced a decrease in water content and weight loss but still had a high average value of moisture content and weight loss. The result of the decrease in moisture content and weight loss affected the hardness of sweet corn, color, and cooling rate. The best treatment combination was obtained in the hydro cooling treatment for 2 minutes with Polypropylene (H2P1) packaging with a weight loss value of 0.33%, hardness 34.20 N / mm2, color L 50.00, a 16.69, b 51.81, water content 74.167%, and a cooling 2.3982 o C / 30 minutes.